Pengaruh Intervensi Emosi Positif pada Pengobatan Fibromyalgia - Romaito Nasution; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Ika Sandra Dewi; Milna Sari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
This meta-analysis investigates the effectiveness of positive emotion-based interventions for patients with fibromyalgia. From a total of 1,247 identified articles, 32 studies (N=2,456 participants) met the inclusion criteria. The results indicate that positive emotion-based interventions significantly reduce pain intensity (g=-0.42, 95% CI [-0.56, -0.28], p<0.001), enhance quality of life (g=0.38, 95% CI [0.25, 0.51], p<0.001), and alleviate depressive symptoms (g=-0.35, 95% CI [-0.48, -0.22], p<0.001). Furthermore, moderator analysis reveals that the duration of the intervention significantly moderates its effects on pain intensity (β=-0.03, p=0.02) and quality of life (β=0.04, p=0.01) in fibromyalgia patients. Among the interventions, mindfulness-based approaches appear most effective in reducing pain (g=-0.51), while cognitive-behavioural therapy shows the greatest efficacy in improving quality of life (g=0.45). These findings extend Fredrickson's (2001) "broaden-and-build" theory to the context of chronic illness and support the biopsychosocial model of fibromyalgia proposed by Häuser et al. (2010). The researchers argue that these results align with Zautra et al. (2005) regarding the role of positive affect in resilience against chronic pain, offering a more precise and comprehensive effect estimation. Unlike previous meta-analyses focused on specific interventions (e.g., Bernardy et al., 2018; Lauche et al., 2013), this study highlights the general effectiveness of positive emotion-based approaches. Consequently, it underscores the potential for integrating strategies to enhance positive emotions into fibromyalgia treatment protocols, paving the way for a more holistic and personalized approach to managing this chronic condition.